Estimation of energy expenditure in professional cyclists using power data: validation against doubly-labelled water - Van Hooren, B. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Accurate determination of total daily energy expenditure (TDEE) in professional cyclists is important to inform on appropriate energy intake, which in turn is required for optimal performance and injury prevention [1]. Current approaches of determining TDEE are however insufficiently accurate as they typically use basal metabolic rate (BMR) prediction equations that are developed for non-elite athletes in combination with a generic physical activity level (PAL) value to determine non-exercise energy expenditure (EE). This is combined with exercise energy expenditure (EEE) estimated from power data to determine TDEE. Knowledge about the non-exercise PAL-value and BMR equations for professional cyclists would improve the accuracy of this approach, but are currently unavailable. We therefore aimed to 1) determine the non-exercise PAL-value during training and competition based on power data in combination with a measured BMR and doubly-labelled water (DLW), and 2) compare outcomes between a multi-day cycling competition (Vuelta a España) and single-day races (Ardennes classics).